Flexible Credit Line : Operational Guidance Note. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
This note provides general guidance on the use of the Flexible Credit Line (FCL). After an overview of the instrument, explaining its specific nature, the operational issues are grouped into three areas: -- an outline of the process and specific steps that need to be followed if a member expresses interest in an arrangement; -- guidance on determining qualification of a member; and -- a how-to guide for determining appropriate access levels. The note is an aid to the implementation of the policy and its underlying principles. If there is any instance in which a provision of the guidance note or its implementation conflicts with Board policy, Board policy prevails. It will be revised as needed, for example following relevant policy reviews.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Arrangement; FCL Arrangement; FCL; PP; Staff; Poland, Republic of